Under the State's Thumb: Results from an Empirical Survey of Civic Organizations in Vietnam - Jörg Wischermann; Bui The Cuong; Nguyen Quang Vinh; Dang Thi Viet Phuong; Nguyen Thi Minh Chau (German Institute of Global and Area Studies (GIGA), 2015)
Civic organizations (COs) are neither a good nor a bad thing. They are not inherently fighters for democracy or supporters of authoritarian rule. The way they develop depends on the impact that various forms of state power have on them and on their influence on the state. Vietnamese COs appear to be no exception. When we examine just one direction of these interdependent and reciprocal relations, it becomes clear that under the constraints of the Vietnamese state's infrastructural power many Vietnamese COs develop features of intra-organizational authoritarianism; that they help to embed the state and the Communist Party more deeply within Vietnamese society; and, finally, that they contribute to bringing the society further under the control of the state and the party. However, this occurs to a very different degree depending on the type of CO. NGOs and faith-based organizations in particular, at least in the field of gender norms and practices, seem to resist the state's discursive power. This could imply challenges to the state's and the party's control of politics and society and leads the authors to draw far-reaching conclusions as far as developmental cooperation with and potential support for various types of Vietnamese COs is concerned.
Keywords: 300; civic organizations; authoritarianism; authoritarian state; Vietnam